(untitled) (Scientific journal of the Fergana State University, 2025)
The article studies the theoretical and methodological foundations of the formation and development of regional tourist and recreational systems, methods for organizing regional tourist and recreational systems and assessing their effectiveness, the role and importance of regional tourist and recreational systems in the effective use of tourist and recreational potential. Also, methods for assessing regional tourist and recreational systems are analyzed.